All we were promised : a novel - Lattimore, Ashton (Ballantine Books, 2024)
"The paths of three young Black women in pre-Civil War Philadelphia unexpectedly--and dangerously--collide in this dramatic debut novel inspired by the explosive history of a city at war with itself. Philadelphia, 1837. When nineteen-year-old Charlotte escaped from the deteriorating White Oaks plantation four years ago, she'd expected freedom to look completely different from her former life as an enslaved housemaid. Instead, she's locked away playing servant to her white-passing father, hiding their past and identities to protect themselves from slavecatchers who would destroy their new lives. Charlotte longs to break away, but outside the walls of their townhouse, the City of Brotherly Love is up in arms. Pennsylvania is a free state, yet abolitionists are struggling to establish a permanent home for the anti-slavery movement, as southern sympathizers incite violence against free Black people and white vigilantes stalk the streets. Undeterred, Charlotte sneaks out and forges an unlikely friendship with Nell, a member of one of Philadelphia's wealthiest Black families. Nell is under so much pressure from her parents to settle down and marry Alex, a close family friend, that the two pretend to get engaged, just to take the heat off. Meanwhile Nell and Charlotte grow close over their mutual commitment to abolition, so when Evie, Charlotte's enslaved friend from White Oaks, shows up in the city, they conspire to help her flee North. Charlotte and her father's freedom is threatened as she and Nell navigate the abolitionist world's racial and class politics and ever-present dangers, struggling to forge a plan to free Evie from slavery before it's too late. Inspired by the untold history of Pennsylvania Hall, one of Philadelphia's landmarks lost to violence, All We Were Promised is the story of three young Black women--the rebel, the socialite, and the fugitive--fighting for each other in an American city straining to live up to its loftiest ideals"--